The Impact of Foreign Direct Investment, Trade Openness, Technological Innovation and Industrial Sector Performance on Economic Growth in Vietnam - Phuc, Doan Ngoc (Journal of Posthumanism, 2025)
This study employs an Autoregressive Distributed Lag (ARDL) model to assess the impact of foreign direct investment, trade openness, technological innovation, and industrial sector performance on economic growth in Vietnam during the period 1993-2023. The results show that, in the short run, foreign direct investment, trade openness, and industrial sector performance have positive impacts on economic growth, while technological innovation has a negative impact. In the long run, foreign direct investment and technological innovation positively affect economic growth, whereas trade openness and industrial sector performance have negative impacts. Based on these findings, the study suggests several policy implications: prioritizing the attraction of foreign investment projects that utilize modern technologies; promoting comparative advantages in international trade; diversifying export markets; restructuring production towards the development of high-tech industries; and fostering technological innovation to generate new technologies and knowledge, thereby supporting rapid and sustainable economic growth.